1992
DOI: 10.1104/pp.100.1.509
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Biosynthesis during Seed Germination in Phaseolus vulgaris

Abstract: The relative roles of de novo biosynthesis of indoleacetic acid (IAA) and IAA conjugates stored in mature seeds (Phaseolus vulgaris L.) in supplying auxin to germinating bean seedlings were studied. Using 2H oxide and 2,4,5,6,7-[2H1L-tryptophan as tracers of IAA synthesis, we have shown that de novo biosynthesis of IAA, primarily from tryptophan, is an important source of auxin for young bean seedlings. New synthesis of IAA was detected as early as the second day of germination, at which time the seedlings beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 24 publications
(37 reference statements)
2
50
0
2
Order By: Relevance
“…However, other bean tissues contain proteins that are detected by Ab3.6K (data not shown). Previous analytical results from our laboratory (22) showed that proteins with IAA attached are present in vegetative tissues of bean, but these earlier reports did not determine the characteristics of the protein moiety. The absence of iap1 mRNA in vegetative tissues (Fig.…”
Section: Plants Contain Phytohormones In Conjugated Formsmentioning
confidence: 69%
See 1 more Smart Citation
“…However, other bean tissues contain proteins that are detected by Ab3.6K (data not shown). Previous analytical results from our laboratory (22) showed that proteins with IAA attached are present in vegetative tissues of bean, but these earlier reports did not determine the characteristics of the protein moiety. The absence of iap1 mRNA in vegetative tissues (Fig.…”
Section: Plants Contain Phytohormones In Conjugated Formsmentioning
confidence: 69%
“…8). Unlike maize (20,21), bean seedlings begin de novo IAA biosynthesis within the first hours after imbibition in the dark (22).…”
Section: Even Though Earlier Work Bymentioning
confidence: 99%
“…It appears that the competence to respond to exogenous auxin is under developmental control which coincides with the initiation of de novo IAA biosynthesis in the growing seedling. Bean seedlings start to synthesize IAA de novo between day 2 and day 3 after imbibition (Bialek et aL, 1992). The need for auxin by the germinating embryo is provided for by the seed.…”
Section: Auxin-responsiveness Of Expressionmentioning
confidence: 99%
“…N, was used to reduce the volume of the pentane to about 1 niL, and the indole content was determined by GC-MS monitoring ions at m/z 117 and 123 (the molecular ions for indole and ['H,]indole, respectively). Because of the low mrichment of the internal standard, the major peak was for I 'H,]indole rather than for ['H,]indole (see Bialek et al, 1992, for calculations). The correction factor ("R value"; C'ohen et al, 1986) for indole measured at m/z 117 and the internal standard measured at m/z 123 was determined 2mpirically to be 1.65.…”
Section: 4mentioning
confidence: 99%
“…The methanol was then removed in vacuo and the derivatized amino acid was dissolved in distilled water. A Fisher PrepSep C,, SPE column and a Waters (Milford, MA) NovaPak C,, HPLC column (on a Varian [Sunnyvale, CAI 5000 HPLC) were used for further purification before analysis by GC-MS (Hewlett-I'ackard 5890 series I1 GC with a Hewlett-Packard 5971A mass selective detector), as described by Bialek et al (1992).…”
Section: Trp Analysismentioning
confidence: 99%